Teachers' competencies in basic geography via distance learning a case study - Roderos, Marlou G. (2006)
Distance education is a rapidly developing approach to instruction worldwide. This study aimed to find out gains of instruction of teachers' competencies in basic concepts in geography usiing distance learning modules and materials. Case study-modular approach and pretest-posttest methodologies were utilized. An orientation program was held on January 14, 2006 and an evaluation process on February 11, 2006 while participants worked on their own on the module via distance learning between these dates. Results showed that there was an increase in the level of performance and understanding of the teachers' knowledge in basic geography concepts as shown in the SAQs given to the teacher-respondents.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Geography -- Study and teaching -- Philippines -- Calapan (Oriental Mindoro); Geography teachers -- Rating of -- Philippines -- Calapan (Oriental Mindoro); Teacher effectiveness -- Philippines -- Calapan (Oriental Mindoro); Distance education -- Philippines -- Calapan (Oriental Mindoro)